2016
DOI: 10.1186/s13104-016-1993-7
|View full text |Cite
|
Sign up to set email alerts
|

Nodding syndrome and epilepsy in onchocerciasis endemic regions: comparing preliminary observations from South Sudan and the Democratic Republic of the Congo with data from Uganda

Abstract: BackgroundNodding syndrome (NS) is an epilepsy disorder occurring in children in South Sudan, northern Uganda and Tanzania. The etiology of NS is unknown, but epidemiological studies demonstrate an association between NS and onchocerciasis.MethodsBetween November 2013 and July 2015 we visited onchocerciasis endemic regions in South Sudan, Uganda, and the Democratic Republic of the Congo (DRC) to assess the epilepsy situation. In South Sudan we interviewed patients and affected families, health officials, colle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
65
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 57 publications
(67 citation statements)
references
References 32 publications
1
65
1
Order By: Relevance
“…In a study in Cameroon, the prevalence of epilepsy and the community microfilarial load (the geometric mean number of Onchocerca volvulus (OV) microfilariae per skin snip among adults aged 20 years and over in the community) were closely related, and microfilarial loads in patients with epilepsy were significantly higher than in controls [3]. In villages in onchocerciasis endemic regions in the Democratic Republic of the Congo, we observed a prevalence of epilepsy of >2% [4], while prevalence in nonendemic African regions is <1% [5].…”
Section: Ns: a Neurologic Disease Affecting African Childrenmentioning
confidence: 71%
See 1 more Smart Citation
“…In a study in Cameroon, the prevalence of epilepsy and the community microfilarial load (the geometric mean number of Onchocerca volvulus (OV) microfilariae per skin snip among adults aged 20 years and over in the community) were closely related, and microfilarial loads in patients with epilepsy were significantly higher than in controls [3]. In villages in onchocerciasis endemic regions in the Democratic Republic of the Congo, we observed a prevalence of epilepsy of >2% [4], while prevalence in nonendemic African regions is <1% [5].…”
Section: Ns: a Neurologic Disease Affecting African Childrenmentioning
confidence: 71%
“…In Mvolo, a village in South Sudan, we found that one in six children suffered from OAE and 50% of the families had at least one child with OAE [4]. Children are the social security of the family in these regions, therefore, having one or more affected children in the family has a huge impact on the family income and status.…”
Section: The Following Key Research Questions Remain To Be Answeredmentioning
confidence: 95%
“…In this situation, because children with OAE will become adults and very few new children will develop OAE, the highest prevalence of epilepsy will be observed among the age group between 20 and 30 years and not among the 10‐ to 20‐year age group before the introduction of CDTi . In most places in Africa, epilepsy is associated with increased mortality because children with epilepsy often die at a young age from drowning, burn injuries, status epilepticus (itself due to lack of access to anti‐epileptic treatment), or neglect, malnourishment, or infections …”
Section: Epidemiological Aspectsmentioning
confidence: 99%
“…Most patients with OAE present with generalized primarily tonic‐clonic seizures, clinically not different from seizures of another etiology. The main differences between OAE and other forms of epilepsy are the time of onset, between the ages of 3 and 18 years (mean age 8–12 years), the fact that persons with epilepsy live in villages with high Ov transmission, and the fact siblings in the family often are also affected by epilepsy . The reason why some children present with generalized tonic‐clonic seizures without other symptoms and others present with NS or features of Nakalanga syndrome is not clear.…”
Section: Clinical Aspectsmentioning
confidence: 99%
See 1 more Smart Citation